Rapport (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
Partnership between universities and communities in the co-construction of research issues, application and dissemination of research results for university research and student training.
Keywords: Employability; Business; Communities; Children; Juvenile detention; Juvenile delinquency; Deprivation of Liberty; Preliminary Investigation; Investigation Phase; Enforcement of Decisions; University